Finding Common Language around Educational Equity in a Neoliberali Context - Bierbaum, Lauren (Only in New Orleans, 2015)
The old story states that there was once an emperor so fond of his new clothes that he spent many an hour and occasion showing off his clothes. This emperor cared not for his duties as emperor, except as those duties would allow him to flaunt his new clothing. One day two swindlers arrived and promised the emperor that they would sew the emperor new clothes that were so fine that the emperor would be able to decipher unfit or unintelligent subjects because the fabric would be invisible to those subjects.